Desafios e limitações encontradas por microempreendedores individuais : um estudo na cidade de Guaporé/RS - Piovesana, Caroline Magri (2022)
According to research developed by the IBGE, in mid-2003, Brazil had over ten million informal workers. It’s quite a significant number for the country, since the related taxes and social security contributions weren’t being collected at the source. Therefore, with the objective of bringing a legal character to the informal workers, the Complementary Law 128/2008 was created, establishing the term individual microentrepreneur. Alongside a wide variety of benefits that this law decreed, it can be pointed out the low cost, low-bureacracy, social security rights and reduced tax rates. The main objective of this study was to identify the individual microentrepreneurs from the city of Guaporé-RS, to analise their singularities, difficulties and the challanges these workers face running their business. To achieve the objective, a survey was apllied for the individual microentrepreneurs from the city, and the collected data was processed using the software Microsoft Excel. There are many reasons why to formalize a business, among them are the regularization of the enterprise, low costs, access to social security rights and also, it’s a simple process. In addition, planning the company’s growth, as well as running it and managing the finances, are the greatest difficulties quoted at the survey.